Optimizing the Use and Maintenance of “Dry Powder” Fire Extinguishers for Fire Suppression on the MT. Pangkalan Brandan - Adhiyaksa Eqie Wardana; Anugrah Nur Prasetyo; Muhammad Dahri; Firdaus Sitepu (National Research and Innovation Agency (BRIN Publishing), 2026)
Fire extinguishers are very important to ensure the safe operation of the ship and must meet the applicable regulations, in accordance with the objectives of the Safety of Life at Sea (SOLAS), contains one of the international conventions which contains Operational Readiness and Maintenance of fire extinguishers. fire extinguishers. Fire on board a ship is a serious threat that requires quick and effective handling to prevent major losses. A dry powder type fire extinguisher (APAR) is one of the main solutions in dealing with fires in the maritime environment. However, the effectiveness of APAR depends on optimal use and maintenance. This research aims to optimize the use and maintenance of dry powder ship type APARs in preventing the above fires. The research method involves field surveys on several ships to practice the use and maintenance of APARs. In addition, statistical analysis is used to identify factors that influence APAR performance.